Enhanced Publications in the Netherlands - van Berchum, Marnix (Septentrio Conference Series, 2014)
One of the subjects of the SURFshare programme of SURFfoundation - started in 2007 and ending this year - were Enhanced Publications (in Dutch: 'Verrijkte Publicaties'). The first projects of the programma started with experiments on how to create, store, and access Enhanced Publications. Together with Dutch higher education and research institutions in the next years tools were developed, such as an OJS plugin and a visualizer; 2011 saw several smaller projects were researchers themselves made Enhanced Publications. This presentation will give an overview of these developments of the SURFshare programme.